Psychological and Behavioral Outcomes From the Perspective of Moral Culture: A Study of College Students - Hu, Wen (Frontiers in Psychology, 2022)
Although the issue of moral identity and morality is under investigation from the last many years, there is still need to investigate its role how it promotes behavior. This study tends to extend this string of literature and attempted to investigate the mediating role of moral reasoning between the elements of moral culture and prosocial behavior and psychological wellbeing. For this purpose College students were selected as participants in this study. For this purpose a two wave strategy was followed to collect data. In the first wave of questionnaire distribution, 600 college students were contacted to complete the response. A hidden secret code was allotted to each questionnaire to trace the respondent for second wave. From the distributed six hundred questionnaires, 507 questionnaires were received back. At this stage, demographic characteristics and questions related to both the independent variables were asked from the respondents. While in the next wave 448 questionnaires were received back from the redistributed questionnaires. At this stage questions related to mediating variable and dependent variables were asked from the respondents. After discarding the incomplete and partially filled questionnaires (17 questionnaires) there were left 431 useable responses. These responses were used to run the tests through Structural Equation modeling (SEM) through assessment of measurement and structural model. Results indicate that symbolization promotes positive changes in psychological wellbeing of the students and prosocial behavior of the college students. Moreover, internalization can promote psychological wellbeing. However, impact of internalization on prosocial behavior of the college students has not been found statistically significant. Moreover, it can be safely concluded that moral reasoning has the potency to mediate the relationship of symbolization and psychological wellbeing as well as prosocial behavior. Moral reasoning also mediates the relationship of internalization and psychological wellbeing and prosocial behavior.